PENGARUH PELATIHAN, MOTIVASI, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA RUMAH MAKAN WARUNG MINA DENPASAR - Putra, I Made Indra Purnama (Jurnal Ekonomi dan Bisnis Jagaditha, 2017)
Performance of employees at Warung Mina Denpasar has experienced problems. Problems in employee performance are associated with some constructs such as training, motivation, work environment and morale. The purpose of this research is to know: 1). The effect of training on morale. 2). The effect of training on performance. 3). The influence of motivation on morale. 4). The influence of motivation on performance. 5). Effect of Work Environment on morale. 6). Effect of work environment on performance and 7). Influence Morale on performance. Research data obtained from the questionnaire, which then will be processed through statistical processing methods Partial Least Square (PLS). The population in this research is all employees of Warung Mina Denpasar which amounts to 120 people. After calculated using slovin formula then the sample in this study amounted to 48 people by using the probability sampling method of simple random sampling. This research was conducted at company of Restaurant Warung Mina which located in denpasar region that is peguyangan and renon. The results stated that: 1) Training has positive and insignificant effect on morale. 2) Training has positive and insignificant effect on performance. 3) Motivation has a positive and significant effect on morale. 4) Motivation has positive and significant impact on performance. 5) The work environment has a positive and insignificant effect on morale. 6) Work environment has a positive and significant impact on performance. 7) The spirit of work has a positive and insignificant effect on employee performance.